An investigation of a Qualitative Research course at a U.S. University - Angela L.E. Walmsley (Networks: An Online Journal for Teacher Research, 1999)
Action research is typically performed by people who want to do something to improve their own situation (Sagor, 1992). Often, it is also collaborative, involving participants with different roles in the situation; together they plan, analyze data and discuss the results, and then share the findings with others in a similar field or situation who may be able to benefit from them. While action research can be used in a variety of settings, the project I present here is specific to education and teaching. I carried out an action research project that investigated aspects of a graduate qualitative education research course offered during the summer 1999 session at a U.S. university taught by a professor whom I shall call Dr. Griffith. An important anticipated benefit of this project was the evidence it would provide on students' perceptions of Dr. Griffith's teaching and organization of the course and the opportunity he would then have to make changes in the light of the findings. But as a graduate student nearing the end of her doctoral coursework, I too expected to benefit from the study. In the future, I hope to teach similar types of courses as a faculty member and so, having already taken the course and being familiar with the material, I thought that being a participant observer and carrying out an evaluation of the course would give me useful insights both about graduate teaching and about carrying out action research.